Development of an AI-Based Customer Service Information System for MSME XYZ - Izmi Fitriani; Dwi Fatrianto Suyatno (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2026)
This research aims to develop an Artificial Intelligence (AI)-based customer service information system for MSME XYZ. The study addresses problems in manual customer service processes, including slow response times, repetitive customer inquiries, and unstructured order management that affect operational efficiency and customer satisfaction. The study applies the Research and Development (R&D) method using the Rapid Application Development (RAD) approach. The developed system is a WhatsApp-based AI chatbot integrated with the n8n automation platform, supported by a PostgreSQL database and a web-based dashboard using Budibase. The system provides automated real-time responses, manages product information requests, processes customer orders, and handles customer complaints. System testing was conducted using the Black-Box Testing method to evaluate system functionality. The results indicate that all systems feature operate according to the specified requirements. The implementation of the AI-based chatbot system improves customer service efficiency, reduces manual workload, accelerates response time, and supports digital transformation for MSMEs.